2016
DOI: 10.5812/jjhs.43085
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effectiveness of Cognitive – Behavioral Couple Therapy and Acceptance and Commitment Couple Therapy in the Couple’s Conflict in the City of Isfahan

Abstract: Background: Marriage is a social process that forms the basis and principle of human communication. In many couples, primary positive feelings decrease in time and are replaced by severe conflicts. What is of high importance is the couples' reaction to these problems. Their ability to apply problem-solving skills can be a factor in the improvement of the couples' relationship. Methods: A quasi-experimental study with pretest, posttest design and control group was applied. The statistical population included al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Third-wave psychotherapies [cognitive-behavioral therapies (CBTs)] emphasize issues such as mindfulness, emotions, acceptance, relationships, values, goals, and metacognition. Acceptance and commitment therapy (ACT) is considered to be a component of third-wave CBTs and includes therapies such as integrated mindfulnessbased cognitive therapy and behavioral couple therapy (11). ACT is one of the new cognitive-behavioral interventions that comprise the four approaches of mindfulness, acceptance, commitment, and behavior change.…”
Section: Introductionmentioning
confidence: 99%
“…Third-wave psychotherapies [cognitive-behavioral therapies (CBTs)] emphasize issues such as mindfulness, emotions, acceptance, relationships, values, goals, and metacognition. Acceptance and commitment therapy (ACT) is considered to be a component of third-wave CBTs and includes therapies such as integrated mindfulnessbased cognitive therapy and behavioral couple therapy (11). ACT is one of the new cognitive-behavioral interventions that comprise the four approaches of mindfulness, acceptance, commitment, and behavior change.…”
Section: Introductionmentioning
confidence: 99%
“…On account of ACT investigations, these processes enhance psychological flexibility. In turn, it increases the satisfaction and quality of the marital life, also decreases marital conflicts with a constant impact (Arabnejad et al, 2014;Khanjani Veshki, Shafiabady, Farzad & Fatehizade, 2016). The effects of ACT were evaluated in studies, such as Khanjani Veshki et al (2016), Kavousian, Haniffi & Karimi (2017), as well as Khanei, Jazayeri, Bahrami, Montazeri & Etemadi (2018).…”
mentioning
confidence: 99%
“…In turn, it increases the satisfaction and quality of the marital life, also decreases marital conflicts with a constant impact (Arabnejad et al, 2014;Khanjani Veshki, Shafiabady, Farzad & Fatehizade, 2016). The effects of ACT were evaluated in studies, such as Khanjani Veshki et al (2016), Kavousian, Haniffi & Karimi (2017), as well as Khanei, Jazayeri, Bahrami, Montazeri & Etemadi (2018). These studies revealed that ACT significantly decreased marital conflict and enhanced marital satisfaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation